EFEKTIVITAS MODEL BERMAIN ASYIK SERTA PEMBERIAN REWARD DALAM MENINGKATKAN RASA PERCAYA DIRI ANAK USIA DINI - Sofiah, Eva; Watini, Sri (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2023)
This research stems from the many learning models offered to support the process of learning activities that take place, but some methods or models require validation of the extent to which the model is effectively applied in a lesson through several indicators of success, The purpose of this study was to measure the effectiveness of the ASYIK play model and its rewards in increasing self-confidence in children, with the research subject being class B (5-6 years old) at An Nizhomiyyah Pandeglang Kindergarten, With the method (action research) of classroom action research consisting of one pre-cycle stage, and two measurement cycles referring to the Kemmis and Taggart spiral design. Data collection techniques were conducted through observation, field notes and documentation. It is concluded that the ASYIK model is effective in increasing children's self-confidence. This is evidenced by several cycles that have been carried out and obtained a significant increase, the ASYIK play model and rewarding can build children's confidence in learning activities from the beginning of the activity to the end. If in the learning process before the ASYIK model and its rewards are implemented children look shy and not confident to explore new things, then learning activities immediately change after this model is implemented.